2021
DOI: 10.3389/fpsyg.2021.703468
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, Moral Disengagement and Empathy. A Longitudinal Study Within the Interpersonal Dynamics of Bullying

Abstract: Moral disengagement and empathy have been linked to aggression in traditional bullying. A number of longitudinal studies have focused on how these variables predict aggressive behavior within the dynamics of bullying. However, no conclusive results have been produced as to whether aggressive behavior in bullying can predict lower levels of empathy, and to date, no studies have explored in depth the mediating role of moral disengagement strategies in this relationship, which is the aim of this study. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 59 publications
(71 reference statements)
0
15
0
3
Order By: Relevance
“…La segunda hipótesis fue confirmada. La empatía afectiva y cognitiva, cuya relación con las estrategias de autoengaño moral y otros fenómenos de agresividad ya había sido probada en estudios longitudinales con escolares (Falla et al, 2021), mediaron significativamente en la relación entre la desconexión moral cívica y las actitudes hacia la diversidad cultural. Por tanto, estos hallazgos confirman las complejas relaciones existentes entre la empatía y la moralidad (Chen et al, 2018).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La segunda hipótesis fue confirmada. La empatía afectiva y cognitiva, cuya relación con las estrategias de autoengaño moral y otros fenómenos de agresividad ya había sido probada en estudios longitudinales con escolares (Falla et al, 2021), mediaron significativamente en la relación entre la desconexión moral cívica y las actitudes hacia la diversidad cultural. Por tanto, estos hallazgos confirman las complejas relaciones existentes entre la empatía y la moralidad (Chen et al, 2018).…”
Section: Discussionunclassified
“…Investigaciones previas señalan que los individuos que muestran mayores niveles de desconexión moral tendrán, a su vez, más probabilidades de manifestar una baja capacidad empática, tanto afectiva como cognitiva (Haddock y Jimerson, 2017). Ciertos estudios han evidenciado que la empatía cognitiva se predice por mecanismos de autoexoneración asociados a la minimización de la responsabilidad, la distorsión de las consecuencias y la deshumanización, mientras que las estrategias de reestructuración cognitiva y distorsión de las consecuencias influyen en la empatía afectiva (Falla et al, 2021).…”
Section: La Empatía Como Constructo Mediador De La Desconexión Moral ...unclassified
See 1 more Smart Citation
“…Interestingly, several studies on young victims of cyberbullying [ 45 , 46 , 47 , 48 , 49 ] have also found that adolescents tend to use moral justification as a way to empathize with their aggressors to protect their self-esteem, which could occur in victims of non-consensual intimate image sharing. Cyberbullying and non-consensual sharing of intimate images occur more among adolescents and young adults than older adults, often with females as victims [ 45 , 50 , 51 , 52 , 53 , 54 ], but non-consensual sharing of intimate images might be more evenly distributed among genders [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moral reasoning consistently predicts risky behaviors in why some individuals decide to engage or not engage in risky behaviors [ 30 ]. Similarly, different patterns of violence are associated with different levels of moral disengagement [ 31 ]. The levels of moral maturity may contribute to correct and preferable decision-making to increasing exhibition of an undesired behavior, as compared to egocentric action.…”
Section: Introductionmentioning
confidence: 99%